Academic activity report as a strategy for learning research (Revista Latino-Americana de Enfermagem, 2005)
This study aimed to analyze academic activity reports about the structure and mental abilities developed by graduate students of two nursing curriculums proposals at a Brazilian university. The study was based on 83 students: 39 from the Transition Curriculum (group I) and 44 from the Integrated Curriculum (group II). Data were collected through a registration card with topics from the December 2002 report by group I and the December 2003 report by group II. The results, presented as frequency percentages, showed that group II elaborated the academic activity report with a better structure than group I. This group also developed a more complex reasoning, especially in the "development" topic. Interventions with group II present a better development in this teaching strategy.